2004
DOI: 10.1007/bf03018427
|View full text |Cite
|
Sign up to set email alerts
|

The threshold current in the intrathecal space to elicit motor response is lower and does not overlap that in the epidural space: a porcine model

Abstract: P Pu ur rp po os se e: : Using electrical epidural stimulation, a current of 1 to 10 mA is required to confirm the presence of the tip of an epidural catheter in the epidural space. The purpose of this study was to examine the hypothesis that the threshold current required to elicit a motor response in the intrathecal space is significantly lower than that in the epidural space in a porcine model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…13,15 In those studies, 3.6 ± 0.6 mA (mean ± SD) was required to cause muscle twitching in response to electric stimulation applied in the epidural space at several levels of the spinal cord (C7, T14-15, L6-7, and S4). In the present study, the MET was 0.3 ± 0.07 (mean ± SEM), one-tenth that found in pigs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,15 In those studies, 3.6 ± 0.6 mA (mean ± SD) was required to cause muscle twitching in response to electric stimulation applied in the epidural space at several levels of the spinal cord (C7, T14-15, L6-7, and S4). In the present study, the MET was 0.3 ± 0.07 (mean ± SEM), one-tenth that found in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Then a stimulus with a frequency of 1 Hz, pulse width of 0.1 milliseconds, and current of 5 mA was applied to the needle as described. 13,15 Then nerve stimulation was started, and when hind limb muscle twitching was present, electric current was decreased by 0.3 mA until no muscle twitching could be seen. Then the current was increased by 0.3 mA to reestablish muscle response; this value was recorded as the MET.…”
Section: Methodsmentioning
confidence: 99%
“…However, the inability to aspirate blood or cerebrospinal fluid is not an absolute indication that an epidural needle or catheter is not in the intrathecal or intravascular space. The use of electrical stimulation for epidural anesthesia may not only be useful to confirm epidural catheter placement, but the threshold current for motor response may also predict intrathecal placement (33,38,50,51). When a catheter is situated properly within the epidural space, a current much greater than 1 mA should be required to elicit muscle twitches (30,31,52).…”
Section: Clinical Applications Detecting Intrathecal and Intravasculamentioning
confidence: 99%
“…As previously mentioned, inadvertent intrathecal or intraneural needle placement may possibly be identified by patient reports of paresthesia or pain upon injection. Because pediatric patients are deeply sedated or under general anesthesia during placement of the neuraxial block, the electrical stimulation test may be an additional safety measure to alert the clinician of needle proximity to the intrathecal space, spinal cord or nerve root (50,61). Thus, while it may not be advantageous for catheter placement verification with these blocks, electrical stimulation may still be useful.…”
Section: Clinical Applications Detecting Intrathecal and Intravasculamentioning
confidence: 99%
“…20 Alternatively, a modification of the Tsui test may be used to facilitate correct spinal needle placement by providing objective information, in addition to the return of CSF via the needle. 21 In previous studies, a different dose-response relationship has been shown in electrical stimulation for the epidural and the intrathecal space. [22][23][24] When it is not clear that returning fluid is CSF, confirmation of placement may be obtained by passing an electrical current through an insulated spinal needle.…”
mentioning
confidence: 95%